2018
DOI: 10.1103/physrevd.97.114019
|View full text |Cite
|
Sign up to set email alerts
|

Hard production of a Z boson plus heavy flavor jets at LHC and the intrinsic charm content of a proton

Abstract: The cross section of associated production of a Z boson with heavy flavor jets in pp collisions is calculated using the SHERPA Monte Carlo generator and the analytical combined QCD approach based on k T factorization at small x and conventional collinear QCD at large x. A satisfactory description of the ATLAS and CMS data on the p T spectra of Z bosons and c jets in the whole rapidity, y, region is shown. Searching for the intrinsic charm (IC) contribution in these processes, which could be visible at large y … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…The ratio falls to unity slowly with increasing E γ T , in the presence of intrinsic charm. Furthermore, measurements of Z /W + c/b production in pp collision at 13 TeV could also give additional significant information on the intrinsic charm contribution [28][29][30][31]. Our study shows that the most important source of theoretical uncertainty on w cc , from the theory point of view, is the dependence on the renormalization and factorization scales.…”
Section: Pdf / Ct14nnloicmentioning
confidence: 71%
See 3 more Smart Citations
“…The ratio falls to unity slowly with increasing E γ T , in the presence of intrinsic charm. Furthermore, measurements of Z /W + c/b production in pp collision at 13 TeV could also give additional significant information on the intrinsic charm contribution [28][29][30][31]. Our study shows that the most important source of theoretical uncertainty on w cc , from the theory point of view, is the dependence on the renormalization and factorization scales.…”
Section: Pdf / Ct14nnloicmentioning
confidence: 71%
“…Recently, the estimation of w cc = 0.34 ± 0.14% was obtained in the NNPDF3.1 analysis [26] based on the global PDF fitting procedure over a wide range of LHC measurements. In our previous publications [27][28][29][30][31], we showed that the IC signal can be visible in the production of prompt photons and vector bosons Z /W in pp collisions, accompanied by heavy-flavor c/bjets at large transverse momenta and the forward rapidity region (|y| > 1.5), kinematics within the acceptance of the ATLAS and CMS experiments at the LHC. Based on our previous results [27][28][29][30][31], in the present paper we investigate the possibility to constrain the intrinsic charm probability using first ATLAS data [32] on measurements of differential cross sections of isolated prompt photons produced in association with a c-jet in pp collision at √ s = 8 TeV.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…This effect is coming from the final state parton showers only, that could be easily understood since in our calculations the initial state parton emissions are already determined from the TMD gluon density and, therefore, do not influence the k T of the gluons. However, parton showers could be very important at some kinematical regions (see, for example, [46,47]).…”
mentioning
confidence: 99%